2017
DOI: 10.21475/ajcs.17.11.03.pne378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of weed flora changes in Portugal in a 10 year basis

Abstract: The aim of this study was to assess the composition of weed communities starting from a rainfed farming system (1997), to the early period of transformation in agricultural systems with the adoption of irrigation (2007). The assessments were made within a 10-year interval and the floristic surveys were conducted in the same georeferenced plots. In 1997, the surveys were mostly performed in winter cereals (wheat, oat, barley), while in 2007, considering the same georeferenced plots, there were winter cereals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Bükün (2005) found that irrigation reshaped the weed flora of cotton fields in the Harran Plain in Turkey and that the frequency of some species changed, whereas new species joined irrigated cotton fields, such as Physalis species. Similar results have been shared by Arslan (2018) in Turkey and Ramôa et al (2017) in Portugal. However, the growers are intended to regrow the same crop again and again using irrigation facilities.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Bükün (2005) found that irrigation reshaped the weed flora of cotton fields in the Harran Plain in Turkey and that the frequency of some species changed, whereas new species joined irrigated cotton fields, such as Physalis species. Similar results have been shared by Arslan (2018) in Turkey and Ramôa et al (2017) in Portugal. However, the growers are intended to regrow the same crop again and again using irrigation facilities.…”
Section: Introductionsupporting
confidence: 85%
“…There were 29 annual species and 8 perennial species (Table 1 to 4). Previous research indicated that Mediterranean basins became foregrounding in terms of weed richness compared to other basins to provide suitable growth conditions for the weeds because of climatic conditions and geological factors (Ramôa et al, 2017;Glemnitz et al, 2006). This richness was more apparent in the survey fields when the number of rare or less frequent species were considered.…”
Section: Weed Flora In 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…Different agricultural practices discussed above may have led to these results. Several studies have reported similar results from different areas around the world (Andreasen et al, 1996;Heap, 2010;Richner et al, 2015 andRamôa et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
“…Richner et al (2015) reported that the arable flora has dramatically altered in response to changing in agricultural practices since the Second World War. Ramôa et al (2017) studied the weed flora changes in response to the modern reformations in agriculture in Portugal. Changes in agriculture practices don't only affect the weed flora of agroecosystems but extends to all biotic and abiotic components (Chamberlain et al, 2000).…”
Section: Introductionmentioning
confidence: 99%